KEKERASAN PERMUKAAN EMAIL GIGI TETAP SETELAH PAPARAN MINUMAN RINGAN ASAM JAWA - Suzanna Sungkar; Sri Fitriyani; Intan Yumanita (Journal of Syiah Kuala Dentistry Society, 2016)
The aim of this study is to know about differences enamel surface hardness of permanent teeth after exposure of tamarind softdrink.This study is experimental laboratories study that use by 15maxillary premolars teeth. Specimen planted in acrylic mould and ground wet to achieve a flat enamel surface using silicon carbide paper, followed by polishing with microns alumina slurry. The surface hardness measurement was done before and after immersion using Knoop hardness tester(Shimadzu HMV 2).Measurement of hardness is done counted three times, that is before soaking with tamarind soft drink, after the first 100 seconds and after seconds soaking for 100 second (total 200 seconds).The achieved data were analyzed using paired t-test (p=0,05). The study showed decrease of hardness after exposure of tamarind soft drink at 100 and 200 seconds statistically shows having meaning deference.Keywords: Erosion, Surface Hardness, Tamarind Soft Drink